Cracking behavior in nodular graphite cast iron under non-proportional cyclic loading. (November 2020) - Kachit, M.; Verdu, C.
Highlights: There was a reduction of fatigue life when the phase shift evolute from 0° or 180° to 90°. Nonsymetric behavior of both fatigue life and crack distribution relatively to δ = 90°. More planes undergoing a tensile cracks mode for δ < 90° than for δ > 90° loads. Abstract: The cracking behavior of ferritic nodular cast iron subjected to multiaxial non-proportional cyclic loading was studied. Crack length increased logarithmically during cycling, with a slop (in µm/cycle) as high as the phase-shift angle (δ) was closing to 90°. A non-symmetrical behavior in terms of fatigue life and crack growth relative to δ  = 90 was observed. The application of analytical method revealed that at all times of the fatigue cycle, the amplitude of principal stresses is much higher for δ < 90° than for δ > 90° contributing thereby to crack growth accelerating, and shortening finally the fatigue life. There were a vast range of critical crystallographic orientations undergoing maximum normal principal stress for δ < 90° than for δ > 90°. Microscopic studies revealed that fatigue cracks did not have strong preferential directions for high-phase angle loads due to the continues rotation of principal directions, so their propagation did not stop.